Shortage of Production Capacity to Meet Market Demand: A Simple Multi-Attribute Rating Technique (Smart) Analysis - Yoyong, Yoyong; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2015)
Abstract.Due to products of PT Bukit Bintan Berjaya are main material for infrastructure and building development, the economic growth will directly raise the demand. This will be very good prospect and challenge for the company to increase its market shares. Therefore, the Company has to maximize its production. At the current condition, the production capacity of the company already reached its maximum capacity which is consist of one unit of rotary and grizzly machine, one unit of crusher (also known as permanent crusher), and one unit of mobile crusher. The company use fishbone diagram to know how to increase the production capacity, and then use Simple Multi-attribute Rating Technique (SMART) analysis to get comprehensive understanding of the decision problem and gain the best alternative to increase production capacity.The study and analysis found that to increase production capacity should be done by add, modify or install additional machine. This happened because the existing crusher machine is too old. With more than 15 years old, the machine frequently need repair and it is difficult to get the spare parts. In addition, the existing mobile crusher cannot produce optimally due to imbalance production output between the first cone crusher with the next cone crusher.The study and analysis also concluded that if the company has more concern in the initial cost and annual cost, the option is alternative G which is not install or modify crushing machines and will keep the production capacity as it is and no need additional initial cost. When the company has more concern in increasing production capacity, the option is alternative A which is install new permanent crushing machines.If the company chooses to increase production capacity with alternative A, it will need to: prepare the time line, prepare schedule and person in charge; prepare the machines and tools; prepare the location; prepare man power; prepare supporting production equipment; and prepare funding and cash flow. The Implementation planned to be done in 6 months.Keywords: multi attribute decision analysis, smart analysis, decision making, fishbone diagram, production shortage